2010
DOI: 10.3109/00498254.2010.512093
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial/lysosomal toxic cross-talk plays a key role in cisplatin nephrotoxicity

Abstract: Cisplatin is widely used chemotherapeutic agent for the treatment of several human malignancies. Dose-related nephrotoxicity is the major adverse effect of cisplatin. The cellular and molecular mechanisms behind the cisplatin nephrotoxicity have not yet been completely understood. In this study, cytotoxic effect of cisplatin on renal proximal tubular (RPT) cells was evaluated. Our results showed that cytotoxic action of cisplatin on RPT cells is mediated by reactive oxygen species (ROS) formation, decline of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…The activation of apoptosis occurs through a mitochondrial membrane potential change and caspase-3 activation 37,38 . Our results support these findings showing that Pt14-Pt16 induces apoptosis in MCF-7 and MDA-MB-231 cells through changing mitochondrial membrane potential.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of apoptosis occurs through a mitochondrial membrane potential change and caspase-3 activation 37,38 . Our results support these findings showing that Pt14-Pt16 induces apoptosis in MCF-7 and MDA-MB-231 cells through changing mitochondrial membrane potential.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al (2001) suggested that short stimulation with hydrogen peroxide could also trigger LMP indirectly by activation of phospholipase A2, leading to degradation of membrane phospholipids. Importantly, several stimuli, such as the aminoglycoside antibiotic gentamicin (Denamur et al 2011), the s2 receptor ligand siramesine (Ostenfeld et al 2005), and the widely used chemotherapeutic agent cisplatin (Pourahmad et al 2010), were also linked to increased ROS production, leading to LMP. Finally, oxidative stress and ROS-dependent LMP were suggested to be especially important in the aging of postmitotic cells (Kurz et al 2007).…”
Section: Lysosomes In Apoptosismentioning
confidence: 99%
“…The utilized doses for ROS scavengers (butylated hydroxytoluen (BHT) and α-tocopherol succinate), MPT pore sealing agents (trifluoperazine and carnitine), ATP generators (l-glutamine and fructose), lysosomotropic agents (methylamine and chloroquine) and CYP450 inhibitors (cimetidine and 4-methylpyrazole) were chosen from similar experiments that were done on rat hepatocytes. [24][25][26] We also investigated the aforementioned doses in our isolation system and perceived that they have maximal protective impacts on the cytotoxicity indicators (data not shown).…”
Section: Animal Care Isolation and Incubation Of Liver Cellsmentioning
confidence: 99%
“…32,33 To do the experiment, a volume of 0.5 ml of the pre-stained (acridine orange 5 ÎŒM) cell suspension was taken and centrifuged at 800× g for 1min. Thereafter, the cell pellet was resuspended in 2ml of incubation medium.…”
Section: Lysosomal Membrane Leakiness Assaymentioning
confidence: 99%